Giant cell tumor of soft tissue of neck: a case report - Trabelsi, Amel (Medknow Publications & Media Pvt Ltd, 2009)
CONTEXT: Giant cell tumor of soft tissue is a rare primary soft tissue tumor with low malignant potential. It is clinically and pathologically similar to the giant cell tumor of the bone. CASE REPORT: We report a case of a 28-year-old man complaining of a painless solitary nodule arising in the spinal muscle of the neck. Computed tomography suggested a neurogenic tumor, but the diagnosis of giant cell tumor was confirmed after detailed pathological examination. The patient remains disease free five months after diagnosis. CONCLUSION: It is important to recognize this pathological entity in order to avoid misdiagnosis with other fibrous tumors associated with giant cells.